Transfer of knowledge, skills and confidence from a faculty development programme for health professions educators into practice. (4th May 2021) - Chia, C. F.; Nadarajah, V. D.; Lim, V.; Kutzsche, S.
Abstract: Background: Faculty development programmes should incorporate the transfer of knowledge, skills, and confidence from the training to educational practice. However, there is a risk that transfer may fail due to inadequate integration of knowledge, skills, and confidence. The study evaluated transfer levels, guided by learned principles from a faculty development programme. Method: The submitted self-reports on a pedagogical intervention of 92 out of 190 health professions educators who participated in a mandatory teaching and learning training programme, were analysed by a mixed-method approach guided by a structured conceptual framework. Results: Overall 93.4% reported the successful transfer of learning. Participants incorporated sustainable changed practice (level A, 57.6%), showed reflection on the impact of changed practice (level B, 21.7%), and performed effect analysis (level C, 14.1%). The rest planned application of learning (level D, 4.4%) and identified gaps in current practice or developed an idea for educational intervention but did not implement (level E, 2.2%). Conclusion: The majority of participants transferred their learning. Faculty development programmes must ensure successful transfer of knowledge, skills, and confidence from the training to educational practice to ensure sustainable development of teaching and learning practices.